ANALISIS PENGARUH JUMLAH UNIT USAHA, INVESTASI DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI PENGOLAHAN BESAR DAN SEDANG DI KOTA SURABAYA TAHUN 2005-2014 - gunawan, kunto inggit; Saputri, Miki Dwi (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRAKThis research entitled "Analysis of Influence Number of Business Unit, Investment and Minimum Wage on Labor Absorption in Sector Large and Medium Manufacturing industry in Surabaya City". The purpose of this study is to determine the effect of Number of Business Unit, Investment and Minimum Wage Against Employment Absorption In Sector Large and Medium Manufacturing Industry in Surabaya City. Types and data sources used a quantitative approach with secondary data in the form of time series data for the 2005-2014 observation period. The research variables consist of dependent variable that is the absorption of manpower in sector large and medium manufacturing industry (Y). The independent variables are the number of business units (X1), Investment (X2) and Minimum Wage (X3). Data analysis tools using multiple linear regression method. Based on multiple linear regression analysis obtained result: Y= 133199,868 + 42,414 X1 -0,001 X2 -0,031 X3 + e. Testing simultaneously obtained value fhitung 52,198 > ftabel 5,79. Obtained also thitung of business unit amounted to 0,835, investment equal to -0,251 and minimum wage equal to -2,898. Thus Ho is rejected and Ha accepted. The conclusion of this research shows that the Number of Business Unit, Investment and Minimum Wage Affect Against Manpower Absorption In Sector Large and Medium Manufacturing Industry in Surabaya City. And the variables that have significant effect on the absorption of manpower in the large and medium industry sector in Surabaya City is the Minimum Wage variable. Keyword : Total Business Units, Investments, Minimum Wages And Employment Planning In The Principles Of Large And Medium Processing Industry